Risk Factors of Infantile Diarrhea (A Case-Control Study) - Iskandar Z. Lubis (Paediatrica Indonesiana, 1992)
From March thru April 1990 an unmatched case-control study had been conducted at the pediatric out-patient Clinic of Dr. Pirngadi Hospital Medan to assess risk factors of infantile diarrhea. The study population were infants, aged younger than 21 months. The mothers of the infants were interviewed, using structured questionnaires. Sample size, calculated by means of formula, with 95 % level of confidence, 90 % power of study, 50% estimated proportion of exposure in the control-group and 2.0 estimated odds ratio, was 121. All infants with diarrhea were included in the case-group until a total number of 124 infants were reached. One control, an infant without diarrhea, was taken for each case from the nearest sequence of attendance after the case. A total of 20 risk factors were tested. Exposure was indicated from the last day before illness. Computerized statistical analysis was performed to calculate odds ratio, 95 % confidence interval and two tailed significance testing for qualitative dichotomic data by means of Chi square test. A total of nine factors were confirmed as risk factors of infantile diarrhea i.e mothers age than 20 years, working mother, not cleaning nipple before suckling the baby bottle feeding, having only one nursing botlle/teat, not ready for use nursing bottle/teat, giving left over supplementary food without reheating, no band-washing before giving supplementary food and malnutrition. The result of this study can be emphasized in health education, especially in diarrheal disease control of infancy; Further well-designed studies are needed.